THE MAIN FEATURE OF THE CONSTRUCTION OF THE UZBEK LANGUAGE - Ruziev Yarash Bozorovich (Researchparks Publishing, 2022)
The article discusses the main features of the construction of German, Russian, Arabic and Uzbek by comparing the stem of the verb in these languages.